COMPARISON OF HADITH STUDIES IN SUNNI AND SYI'AH VIEWS - M. Nur Khotibul Umam; Ahmad Faqih; Mohammad Hasan Azhari (International Conference on Humanity Education and Society (ICHES), 2023)
Hadith has great urgency in Islam. As the second law after the al-Qur’an that has been agreed by the Ulama, the Hadith functions as an explanation for both unclear verses and laws that are not in the al-Qur’an. If there are differences in the concept of hadith, of course, it will have an impact on the resulting legal results. Broadly speaking, the difference in the concept of hadith is divided into two groups, namely Sunni and Syi’ah. The fundamental difference between these two groups is that the Hadith among the Syi'ah does not only come from the Prophet Muhammad as well as the Sunnis, but hadith is everything that relies on the ma'sum. Apart from this concept, according to Sunni, the justice of a friend is fair, while according to Syiah Sahabat it is like an ordinary human who needs to conduct research on it. The classification of hadith according to Shi'ah is not only shahih hasan and dhoif as is sunni, Shia adds the classification of muwassaq. According to syi'ah muwassaq hadiths are traditions that come from groups other than Shi'ah but are recognized as tsiqah. As for the hadith literature that is popular with Sunnis, it is the Sahih bukhari and Muslin books while the Shi'ah use al-Kafi. These differences need to be made comparisons to find out the differences in understanding of hadith;